Pediatric Hepatoblastoma: A Single-Institution Case Series - Jessica Sawaya; Joyce McRae; Georgi D. Mladenov; Andrei Radulescu (University Library System, University of Pittsburgh, 2024)
Introduction: Hepatoblastomas comprise up to two-thirds of malignant liver masses in childhood and rank as the third most common malignant neoplasm in children under the age of three. Treatment and prognosis are highly dependent on tumor staging and characteristics. Our study's aim is to analyze the clinical findings and outcomes of hepatoblastoma at our institution. Methods: After Institutional Review Board (IRB) approval was granted from Loma Linda University #5240020, we conducted a retrospective review on all patients under the age of 18 with a diagnosis of hepatoblastoma between February 2000 to January 2022. Variables assessed included demographics, work up, surgical intervention, recurrence, and mortality. Results: Fifteen patients were diagnosed with hepatoblastoma in that timeframe. Mean age was 18.7 months. Associated comorbidities included three patients with prematurity, one patient with Beckwith-Wiedemann Syndrome, and two unique presentations each of Prune Belly Syndrome and grade IV/V vesicoureteral reflux. There were four mortalities, two due to relapse in disease, one due to pulmonary and CNS metastasis at diagnosis, and another due to sepsis and multi-organ failure. Eleven patients continued monitoring without tumor recurrence. All patients were treated based on the Children's Oncology Group (COG) guidelines. Conclusion: Risk stratification is an important component of hepatoblastoma management. Our cohort demonstrated novel comorbidities of Prune Belly Syndrome and vesicoureteral reflux. Eleven patients received neoadjuvant chemotherapy that allowed for subsequent surgical resection. Our mortalities were associated with tumor metastasis and recurrence consistent with elevated alpha-fetoprotein (AFP) values. Future research should involve multi-institutional studies focusing on comorbidities and genetic analysis.